Investigation about the efficiency of the bioaugmentation technique when applied to diesel oil contaminated soils - Mariano, Adriano Pinto [UNESP]; Angelis, Dejanira de Franceschi de [UNESP]; Pirôllo, Maria Paula Santos [UNESP]; Contiero, Jonas [UNESP]; Bonotto, Daniel Marcos [UNESP] (Brazilian Archives of Biology and Technology, 2009)
Este trabalho investigou a eficiência da técnica do bioaumento quando aplicada a solos contaminados com óleo diesel coletados em três postos de combustíveis. Experimentos de biodegradação foram realizados em frascos de Bartha (250 mL), usados para medir a produção microbiana de CO2. A eficiência de biodegradação também foi quantificada pela concentração de hidrocarbonetos. Conjuntamente aos experimentos de biodegradação, a capacidade das culturas estudadas e dos microrganismos nativos em biodegradar óleo diesel comprado de um posto de combustíveis local, foi verificada utilizando-se a técnica baseada no indicador redox 2,6 - diclorofenol indofenol (DCPIP). Resultados obtidos com esse teste mostraram que os inóculos empregados nos experimentos de biodegradação foram capazes de biodegradar óleo diesel e os testes com os microrganismos nativos indicaram que estes solos previamente apresentavam uma microbiota adaptada para degradar hidrocarbonetos. em suma, nenhum ganho foi obtido com a adição dos microrganismos ou mesmo efeitos negativos foram observados nos experimentos de biodegradação.

This work investigated the efficiency of the bioaugmentation technique when applied to diesel oil contaminated soils collected at three service stations. Batch biodegradation experiments were carried out in Bartha biometer flasks (250 mL) used to measure the microbial CO2 production. Biodegradation efficiency was also measured by quantifying the concentration of hydrocarbons. In addition to the biodegradation experiments, the capability of the studied cultures and the native microorganisms to biodegrade the diesel oil purchased from a local service station, was verified using a technique based on the redox indicator 2,6 -dichlorophenol indophenol (DCPIP). Results obtained with this test showed that the inocula used in the biodegradation experiments were able to degrade the diesel oil and the tests carried out with the native microorganisms indicated that these soils had a microbiota adapted to degrade the hydrocarbons. In general, no gain was obtained with the addition of microorganisms or even negative effects were observed in the biodegradation experiments.
Keywords: bioremediation; bioaugmentation; soil; diesel oil; service station